This is how it always is - Frankel, Laurie (Flatiron Books, 2017)
"This is how a family keeps a secret...and how that secret ends up keeping them. This is how a family lives happily ever after...until happily ever after becomes complicated. This is how children change...and then change the world. When Rosie and Penn and their four boys welcome the newest member of their family, no one is surprised it's another baby boy. At least their large, loving, chaotic family knows what to expect. But Claude is not like his brothers. One day he puts on a dress and refuses to take it off. He wants to bring a purse to kindergarten. He wants hair long enough to sit on. When he grows up, Claude says, he wants to be a girl. Rosie and Penn aren't panicked at first. Kids go through phases, after all, and make-believe is fun. But soon the entire family is keeping Claude's secret. Until one day it explodes. This Is How It Always Is is a novel about revelations, transformations, fairy tales, and family. And it's about the ways this is how it always is: Change is always hard and miraculous and hard again; parenting is always a leap into the unknown with crossed fingers and full hearts; children grow but not always according to plan. And families with secrets don't get to keep them forever"--